PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PEGAWAI DI UPTD PUSKESMAS HILISIMAETANO KECAMATAN MANIAMOLO KABUPATEN NIAS SELATAN - Alfandi Zagoto (Universitas Nias Raya, 2024)
The purpose of this study was to determine the effect of leadership on employee performance, to determine the effect of work motivation on employee performance and the influence of leadership and work motivation on employee performance at the UPTD Hilisimaetano Health Center, Maniamolo District, South Nias Regency. The type of research used in this research is quantitative research. The sample in this study amounted to 42 employees. This study uses data collection techniques by distributing questionnaires to employees. The data analysis method used in this study is multiple linear regression analysis. The results of this study indicate that there is an influence of leadership and work motivation on employee performance. In this study, we obtained multiple linear regression equations, namely: Y = 12.828 + 0.265X1 + 0.366X2 and obtained the t count value for the leadership variable (3.284) > t table (1.697) with a significant level of 0.003 < 0.05 while the t count value for the work motivation variable (3.553) > t table (1.697) with a significant level of 0.001 < 0.05. Then the value of F count (13.184) > F table (3.295) is obtained with a significant level of 0.000 < 0.05. So it can be concluded that leadership and work motivation have a significant effect on employee performance at the UPTD Hilisimaetano Health Center, Maniamolo District, South Nias Regency.